Peripheral visions in the globalizing present : space, mobility, aesthetics - Peeren, Esther; Stuit, Hanneke; Weyenberg, A. van, 1977- (Thamyris intersecting ;, 2016)
This volume sheds new light on how today's peripheries are made, lived, imagined and mobilized in a context of rapidly advancing globalization. Focusing on peripheral spaces, mobilities and aesthetics, it presents critical readings of, among others, Indian caste quarters, the Sahara, the South African backyard and European migration, as well as films, novels and artworks about marginalized communities and repressed histories. Together, these readings insist that the peripheral not only needs more visibility in political, economic and cultural terms, but is also invaluable for creating alternative perspectives on the globalizing present. Peripheral Visions combines sociological, cultural, literary and philosophical perspectives on the periphery, and highlights peripheral innovation and futurity to counter the lingering association of the peripheral with stagnation and backwardness.